Optical absorption of suspended graphene based metal plasmonic grating in the visible range. (2nd May 2018) - Han, Y X; Chen, B B; Yang, J B; He, X; Huang, J; Zhang, J J; Zhang, Z J
Abstract: We employ finite-difference time-domain ( FDTD) method and Raman spectroscopy to study the properties of graphene, which is suspended on a gold/SiO2 /Si grating structure with different trench depth of SiO2 layer. The absorption enhancement of suspended graphene and plasmonic resonance of metal grating are investigated in the visible range using 2D FDTD method. Moreover, it is found that the intensity of the Raman features depends very sensitively on the trench depth of SiO2 layer. Raman enhancement in our experiments is attributed to the enhanced optical absorption of graphene by near-field coupling based metal plasmonic grating. The enhanced absorption of suspended graphene modulated by localized surface plasmon resonance (LSPR) offers a potential application for opto-electromechanical devices.